Odpowiedzi

2009-11-18T12:39:02+01:00
Ze wzoru skróconego mnożenia:
a³+b³ = (a + b) * (a² - ab + b²)
x ³ + 1 =(x+1)(x²-x+1)
27x³+y³ = (3x)³+y³=(3x + y) * ((3x)² - (3x) * y + y²) = (3x + y) * (9x² - 3xy + y²)


a³-b³=(a-b)(a²+ab+b²)

5x³-1³ =(³√5x)³-(1)³=(³√5x-1)(³√5²x²+³√5x+1)
x ³ -2=(x+pier 3 stopnia z 2)(x²-pier 3go stop z 2 razy x+pierwc3 go stop z 2 do kwadratu )
(a+b)³=a³+3a²b+3ab²+b³

(x+2)³=x³+3*x²*2+3*x*2²+2³=x³+6x²+12x+8

(2x+1)³=2³x³+3*2²x²*1+3*2x*1²+1³=8x³+12x²+6x+1

(a-b)³=a³-3a²b+3ab²-b³

(x-3)³=x³-3*x²*3+3*x*3²-3³=x³-9x²+27x-27
2009-11-18T13:09:23+01:00
1. (5x+2)³=125x³+3×(5x)²×2+3×5x×4+8=125x³+150x²+60x+8
(3x+6)³=27x³+3(3x)²×6+3×3x×36+216=27x³+162x²+324x+216
2.(3x-4)³=27x³-3(3x)²×4+3×3x×16-64=27x³-108x²+144x-64
(½x-2)³=⅛x³-3(½x)²×2+3×½x×4-8=⅛x³-¾x²×2+6x - 8= ⅛x³-1½x²+6x-8
3. 64x³-8=(4x-2)(16x²+4x×2+4)=(4x-2)(16x²+8x+4)
27x³-125=(3x-5)(9x²+3x×5+25)=(3x-5)(9x²+15x+25)
4.343x³+8=(7x+2)(49x²-7x×2+4)=(7x+2)(49x²-14x+4)